PENGARUH BUDAYA KOREA TERHADAP GAYA HIDUP DAN NILAI KEISLAMAN MAHASISWA FAKULTAS PENDIDIKAN OLAHRAGA DAN KESEHATAN - Ridho Setiawan, Muhamad; Abdulatif, Anwar Akhmad; Azfa Priatna, Kiki Alghifari; Meliana, Nisa; Muhimaturohmah, Siti; Abdillah, Hilman Taufiq (Jendela Inovasi Daerah, 2025)
Korean culture through music, drama, and fashion has become a global phenomenon that influences the lifestyle and Islamic values ​​of students. This study analyzes the influence of Korean culture on the lifestyle and Islamic values ​​of FPOK students using a quantitative approach with a Likert scale questionnaire on 62 respondents. The results of the analysis showed good validity and reliability (Cronbach's Alpha X = 0.782, Y1 = 0.806, Y2 = 0.856). Pearson correlation showed a significant relationship between Korean culture and lifestyle (r = 0.622, p < 0.01) and Islamic values ​​(r = 0.506, p < 0.01). Regression analysis showed that Korean culture explained 38.7% of the variation in lifestyle and 25.6% of Islamic values. These results indicate that Korean culture has a significant influence on students' lifestyle, but the influence on Islamic values ​​is weaker. These findings emphasize the importance of considering other factors in understanding changes in students' lifestyle and Islamic values.